A new species of Clavaria from India - K, Krishnapriya; Arun Kumar, T.k. (Phytotaxa, 2023)
A new species of clavarioid fungi, Clavaria viriditincta is described from Kerala State, India. This species is proposed as new based on morphological and molecular phylogenetic (ITS-LSUsequence) data. C. viriditincta can be distinguished from all other described species in the genus by its distinctly green, unbranched basidiomata, and by its genetic distinctiveness.